1991
DOI: 10.1152/jappl.1991.70.6.2508
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory-related recruitment of the masseter: response to hypercapnia and loading

Abstract: To test the hypothesis that a muscle that closes the jaw, the masseter, can be recruited by ventilatory stimuli, we studied the electromyographic activation of the masseter and genioglossus in seven normal awake males who were exposed in random order to progressive hyperoxic hypercapnia, inspiratory threshold loading (-40 cmH2O), and combined hypercapnia and loading. With hypercapnia, the masseter was generally recruited after the genioglossus had been activated. Once recruited, activation of both muscles incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…Interestingly, trigeminal motoneurons display rhythmic respiratory activity in newborn rodents (e.g. Jacquin et al, 1999;Koizumi et al, 1999Koizumi et al, , 2002 and even in humans especially under particular conditions (Sauerland et al, 1981;StJohn and Bledsoe, 1985;Hollowell and Suratt, 1989;Hollowell et al, 1991). These findings may possibly account for the persistence of vestiges of the original trigeminal oscillator and for the high homology between the pTRG and the preBötC.…”
Section: Considerations On the Evolutionary Trends In Respiratory Rhymentioning
confidence: 99%
“…Interestingly, trigeminal motoneurons display rhythmic respiratory activity in newborn rodents (e.g. Jacquin et al, 1999;Koizumi et al, 1999Koizumi et al, , 2002 and even in humans especially under particular conditions (Sauerland et al, 1981;StJohn and Bledsoe, 1985;Hollowell and Suratt, 1989;Hollowell et al, 1991). These findings may possibly account for the persistence of vestiges of the original trigeminal oscillator and for the high homology between the pTRG and the preBötC.…”
Section: Considerations On the Evolutionary Trends In Respiratory Rhymentioning
confidence: 99%
“…It has been demonstrated that in patients with OSA there is a greater fall in the GG EMG activity in comparison with controls, with the onset of sleep (Mezzanotte et al, 1996;Yoshida, 1998;Fogel et al, 2005). It has been reported that the M muscle has generally been recruited to aid the stabilization of the mandible following the activation of the GG muscle, thus allowing GG to function more effectively as a airway dilatory muscle (Hollowell et al, 1991). It would therefore appear that this witnessed augmentation in activity would indeed be beneficial in OSA subjects and support a physiological role to their action.…”
Section: Muscles Medianmentioning
confidence: 99%
“…Yoshida (1998) also reported an increase in M muscle activation with the placement of the MAS in asleep OSA patients. It has been reported that the M muscle has generally been recruited to aid the stabilization of the mandible following the activation of the GG muscle, thus allowing GG to function more effectively as a airway dilatory muscle (Hollowell et al, 1991). Much of the available literature surrounding M EMG studies relates to functional appliance studies in children (Miralles et al, 1988;Sessle et al, 1990;Aggarwal et al, 1999).…”
Section: Muscles Medianmentioning
confidence: 99%
“…However, patients with OSA already show increased upper airway dilator muscle activity during wakefulness compared with normal subjects (Mezzanotte et al, 1996). The selection of the nonlinear control function gain in equation (26) was based on medical data on activation of genioglossus (GG) during progressive hypercapnia (Hollowell et al, 1991). There is also evidence of a nonlinear relationship between ventilation rate and EtCO 2 (Noshiro et al, 1993) and ventilation rate and SaO 2 (Kirby et al, 1994).…”
Section: Discussionmentioning
confidence: 99%